The role of CTRP9 on Inhibition the High-glucose-induced Apoptosis of Myocardial Cells via Wnt/β-catenin Signal Pathway - Zhang, Qian; Pei, Liying; Fu, Jiali; Zhao, Rui (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effect of CTRP9 regulating the Wnt/β-catenin signal pathway on the high-glucose-induced apoptosis of myocardial cells. For this purpose, high glucose was used to establish the myocardial cell apoptosis models on H9c2 cells which were later divided into 11 groups, with different treatments: NG group, NG+C group, NG+SKL group, NG+SKL+C group, NG+C59 group, HG group, HG+C group, HG+SKL group, HG+SKL+C group, HG+C59 group and HG+4h C group. Following the treatment, a TUNEL assay was applied to determine the apoptotic rate of cells, and RT-PCR and Western blot were carried out to determine the expression of targeted proteins or genes and the activity of the Wnt/β-catenin signal pathway. In comparison with the cells in the NG group, cells following the 48 hours of treatment with 25 mmol/L high glucose experienced an acute increase in the apoptotic rate, with upregulation of Caspase-3 and Bax and downregulation of Bcl-2. In addition, CTRP9 treatment for the high-glucose-treated myocardial cells partially reversed the effect of single treatment by high glucose, with manifestations of decreased apoptotic rate, downregulation of caspase-3 and Bax, upregulation of Bcl-2 and inhibition of Wnt/β-catenin signal pathway. Furthermore, SKL2001, the agonist of the Wnt/β-catenin signal pathway, was added into the high-glucose-treated cells and increased the apoptotic rate, with the activation of the Wnt/β-catenin signal pathway, which, however, was reversed by the treatment of CTRP9. In general, CTRP9, by inhibiting the activity of the Wnt/β-catenin signal pathway, can alleviate the high-glucose-induced apoptosis of myocardial cells.